6x – 4y = 9
4y = 6x - 9
y = 6/4 x - 9/4
y = 3/2 x - 9/4 this line has slope = 3/2
perpendicular line, slope is opposite and reciprocal so slope of this line = -2/3
answer:
A. y= - 2/3 x - 4 (only this line has slope = -2/3)
Answer:
the solution of the system is:
x = 1 and y = 2.
Step-by-step explanation:
I suppose that we want to solve the equation:
-6*x + 6*y = 6
6*x + 3*y = 12
To solve this, we first need to isolate one of the variables in one of the equations.
Let's isolate y in the first equation:
6*y = 6 + 6*x
y = (6 + 6*x)/6
y = 6/6 + (6*x)/6
y = 1 + x
Now we can replace this in the other equation:
6*x + 3*(1 + x) = 12
6*x + 3 + 3*x = 12
9*x + 3 = 12
9*x = 12 - 3 = 9
x = 9/9 = 1
Now that we know that x = 1, we can replace this in the equation "y = 1 + x" to find the value of y.
y = 1 + (1) = 2
Then the solution of the system is:
x = 1 and y = 2.
Answer:
12000(1+.04)^x
Step-by-step explanation:
12000(1+.04)^x
18 - 7x = -20.52.5 = 7xx = 5/14 (c)